2005
DOI: 10.1097/01.mnm.0000183795.59097.42
|View full text |Cite
|
Sign up to set email alerts
|

High pre-therapy [99mTc]pertechnetate thyroid uptake, thyroid size and thyrostatic drugs: predictive factors of failure in [131I]iodide therapy in Graves' disease

Abstract: Fixed doses of 370 MBq of radioiodine seem to be practical and effective for treating Graves' disease patients with [99mTc]pertechnetate uptake <12.5% and thyroid mass <53 g. This treatment is clearly not recommended for patients with large goitre. In contrast to what could be expected, patients with a high pre-RIT thyroid uptake presented a higher rate of RIT failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 32 publications
(60 reference statements)
4
47
2
2
Order By: Relevance
“…16,39,40 Furthermore, other factors, including gland uniformity and pretreatment with ATDs also affect outcome. 41 In our study, almost all our patients were pretreated with ATD, making it an unlikely factor for any differences in therapy outcome.…”
mentioning
confidence: 98%
“…16,39,40 Furthermore, other factors, including gland uniformity and pretreatment with ATDs also affect outcome. 41 In our study, almost all our patients were pretreated with ATD, making it an unlikely factor for any differences in therapy outcome.…”
mentioning
confidence: 98%
“…[1112] The good cure rates with low dose in our study population could be attributed due to relatively small diffused toxic goiters, probable relatively lesser iodine turnover, and persistent iodine-deficient state in a significant segment of Indian population despite universal iodization program implementation. Allahabadia et al ., reported that males are less likely to respond to a single dose of RAI[7] which is in line with study results in group B.…”
Section: Discussionmentioning
confidence: 94%
“…Similar results have also been reported by Zantut-Wittmann et al . [11] In a study by Allahabadia et al . which included 813 patients the authors concluded that male patients with large goiters are more likely not to respond to a single dose of 131 I even with high doses of 370 MBq and are concordant with our results.…”
Section: Discussionmentioning
confidence: 99%